PENYUSUNAN MEDIA PROMOSI BERBASIS INFORMASI DAN TEKNOLOGI UNTUK BALAIYANPUS DPAD DIY - Andriyanti, Erna; Widyastuti, Susana; Sudartinah, Titik (Universitas Mataram, 2024)
DPAD DIY Library Service Center (Balaiyanpus), which provides resources for disseminating knowledge and information, always needs to introduce to the public its three units: Grhatama Pustaka Library, Jogja Library Center, and Modern Learning House. Unfortunately, its promotional materials were limited. To optimize its promotion, the English Literature Study Program of UNY conducted a Community Service (PkM) aiming to develop information technology-based promotional media through creating contents for social media and translating its leaflets from Bahasa Indonesia into English. During preparation, the PkM team conducted a needs analysis and field survey. In development stage, the promotional media were designed by the team, given feedback by Balaiyanpus DPAD DIY, and revised. Afterwards, the translated promotional leaflets were posted on its website and 30 digital contents were broadcast via its Instagram and Tiktok accounts. Evaluation was received from respondents and Balaiyanpus DPAD DIY. The promotional contents were considered informative, interesting, understandable, fairly easy to remember, and appropriate for the social media. An assessment from Balaiyanpus DPAD DIY shows that those contents received a positive response from the public.